Are Some Randomized Clinical Trials Impossible?. Issue 1 (January 2021) - Rios, Jonathan J.; Richards, B. Stephens; Stevenson, David A.; Oberlander, Beverly; Viskochil, David; Gross, Andrea M.; Dombi, Eva; Widemann, Brigitte C.; Plotkin, Scott R.; May, Collin J.; Ullrich, Nicole J.; Goldstein, Rachel Y.; et al.
Abstract : Congenital tibial pseudarthrosis is a rare condition seen in neurofibromatosis type 1 (NF1), and treatment is complex. A randomized, placebo-controlled trial of bone morphogenetic protein (rhBMP-2; INFUSE bone graft) at time of tibial surgery was developed by the Neurofibromatosis Clinical Trials Consortium. Patients were randomized to receive rhBMP-2 that would, or would not, be added to the standard surgical procedure consisting of resection of pseudarthrosis tissue, insertion of a rigid intramedullary rod, and placement of autogenous iliac crest bone graft. Despite involvement of 16 centers with wide experience with NF1 orthopaedic management, only 5 patients (of 54 required) were able to be enrolled in the study during a 3-year time period. Because of the inability to recruit sufficient patients, this study was closed in June 2019, with plans to terminate. The obstacles that were encountered during the study are summarized. The authors question whether a randomized, placebo-controlled trial of a rare pediatric orthopaedic condition is possible to accomplish. Recommendations are provided to guide future studies of orthopaedic manifestations of NF1. Level of Evidence: Level V.